The Effect Of Organizational Culture,Motivation, And Communication On Employee Job Satisfaction With Organizational Commitment As A Moderating Variable At Pt Fan Solusindo Bersama - Muhammad Asyari Syahab; Yusuf Ronny Edward; Salman Faris; Alex Tribuana Sutanto (Publisher Cv. Inara, 2022)
This study aims to determine the effect of organizational culture, motivation, communication and level of knowledge on employee job satisfaction with organizational commitment as a moderating variable. Case study at PT. Fan Solusindo Bersama. Methods of data collection is done through a questionnaire distributed to employees of PT. Fan Solusindo Bersama. This type of research is quantitative research. The object of research used is all employees of PT. Fan Solusindo Bersama. The population in this study were employees of PT. Fan Solusindo Bersama, with a sample of 100 respondents. By using accidental sampling method. The data obtained were then processed with SPSS version 16 and data analysis techniques using validity tests, reliability tests, statistical tests, classical assumption tests and MRA (Moderated Analysis Regression) tests. Based on the Moderated Regression Analysis (MRA) test, it shows that organizational culture, motivation, communication and level of knowledge on employee job satisfaction have a positive and significant effect. Organizational commitment can be a moderating variable of organizational culture, motivation, communication on job satisfaction of employees at PT. Fan Solutions Bersama.